Incidence of Post Dural Puncture Headache (PDPH) after Spinal Anesthesia at Dr. Hasan Sadikin General Hospital Bandung in February–April 2015 Period - , Suwarman; Sitanggang, Rully H.; Mayasari, Ferra; Yuwono, Hendro Sudjono (Perdatin Pusat, 2015)
Post dural puncture headache (PDPH) occurs because of the cerebrospinal fluid leakage caused by dural puncture. Post dural puncture headache is a common complication after spinal anesthesia which incapacitating the patients. The purpose of our study is to describe the incidence of PDPH in patient undergone surgery with spinal anesthesia at Dr Hasan Sadikin General Hospital Bandung and obtaining the risk factor characteristics which associated with PDPH. This cross sectional observational study carried out 156 postoperative subjects with spinal anesthesia patients over February until April 2015. There were 10 subjects (6,41%) developed PDPH. The characteristics which assosciated with PDPH dan statistically significant (p value<0,05) are median and paramedian punctures technique (PR=19,722; CI 95% 6,377; 60,996), history of PDPH (PR=17,222; CI 95% 9,235; 32,469), and multiple punctures (PR=6,400; CI 95% 1,406; 29,132). Whereas, characteristic which associated independently with PDPH is the median and paramedian punctures technique (POR=29,121 CI 95% 33,842;220,745). Anesthesiologist have an important role to prevent PDPH with selection of spinal needle, selection of mastered technique, and improving anesthesiologist’s skill.